Nanomaterials and Their Effects on Health - Gülden Sarı; Birgül Piyal (İstanbul Medical Journal, 2019)

(untitled)
Nanotechnology, which includes many potential applications, is described as the technology of the future and the industrial revolution of the 21st century. The effect of nanotechnology is particularly evident in nanomaterials (NMs) used for chemicals, pharmaceuticals, and personal care products. Properties such as nanoscale size, large surface area, and surface activity make NMs attractive for many applications. It is estimated that more than 1600 nanoscale products are on the market today and that by 2020, more than six million employees will be exposed to engineered nanoparticles (NPs). Due to the observed changes in the physical, chemical, and toxicological properties of the material in parallel with the decreasing particle size, it is predicted that NPs may cause adverse effects on biological systems. However, due to the relative novelty of nanotechnology, there is a lack of knowledge about the ways humans are exposed to NPs and the possible adverse health effects of NPs. Knowledge of the effects of longterm exposure to engineered NPs on human health is based on in vitro studies, in vivo animal studies, and a limited number of human exposure studies. In our country, there are no studies in this field. A better understanding of the health effects of NPs, which is expected to have increased production in our country soon, is a scientific necessity to be dealt with for the safe use of NMs. Therefore, it is aimed to evaluate the effects of NPs on human health in the light of current information and to draw attention to the dangers that may develop.